English Language Learning Using Literary Texts in the Virtual 3D Space of the MaxWhere Seminar System - Tóth, Erzsébet; Boda, István Károly; T. Nagy, László (Central European Journal of Educational Research, 2022)
Through this paper, we will provide a brief overview of the 3D virtual library project and a more detailed review of its current application for English language learning. The implementation of the library project makes use of the innovative 3D presentation features of the MaxWhere Seminar System. As an innovative application of the project, we compiled a bilingual learning material for Hungarian students to improve their language skills and competence in English at an advanced level. The complex structure and organization of the learning material is based partially on the hypertextual relationships between entries of selected keywords containing various contexts from different works of world literature. We developed the learning material taking into careful consideration the appropriate characteristics of the hyperlink structure. Our basic hypothesis was that if the bilingual learning material is organized as a more or less scale-free network of interconnected nodes, this might or would result in an optimized and efficient knowledge transfer in the learning process. After the first version of the material had been completed, we wanted to evaluate the overall difficulty of the material. As such, we were using the Google Translate (GT) service to check the proper understanding of a set of selected English language phrases and sentences through their Hungarian translations provided by GT. As a result, we created a more or less scale-free learning material whose linguistic content has been properly checked.